Detection and Typing of Multiple Genital Human Papillomaviruses by DNA Amplification with Consensus Primers - Yoshikawa, Hiroyuki (Jpn J Cancer Res, 1991)
Many types of human papillomavirus (HPV) are associated with genital lesions. In order to develop simple and sensitive diagnostic procedures for HPV infection, we took advantage of the polymerase chain reaction (PCR). We compared the published nucleotide sequences of the LI region from six genital HPV types and designed a pair of consensus primers for LI region. The PCR with the consensus primers for LI region (Ll‐PCR) could amplify at least nine genital HPV types, 6,11, 16, 18, 31, 33, 42, 52 and 58, and the amplified HPV DNA could be typed by subsequent restriction mapping. Ll‐PCR was compared to Southern blot analysis and also to the consensus primer‐mediated PCR for E6 region (E6‐PCR) described before. Although both our PCR systems are nonradioactive, the sensitivity in detecting HPV DNA was even better than that obtained by using Southern blot analysis. By means of the PCR systems we detected HPV DNA in 100% of cervical condylomas (10/10), 92% of cervical intraepithelial neoplasias (33/36) and 96% of invasive cervical carcinomas (53/55), while we detected HPV DNA in 12% of normal cervices (12/102).